As infâncias em Alegre (ES): a circulação e o brincar de crianças em uma cidade pequena - Joelma Andreão de Cerqueira (2024)
This research aims to analyse the ways children relate with public spaces in a small city in Espírito Santo, Alegre, from their everyday circulation. The specific goals are: (i) to analyse the routes and the reasons of everyday children's circulation, identifying their perceptions of the city; (ii) to identify and analyse children's interaction in and with city spaces; (iii) to register and interpret the use of public spaces from children in the city; (iv) to understand how social markers of difference interfere in different ways of exploring and relating with the city and how distinct childhoods interact with public spaces in a small city. The goal is, by understanding the childhoods and their urban experiences, to collate aspects between the fields of urban studies and childhood studies, especially academic discussions that relate childhood, children and cities, with an emphasis in circulation and appropriation of public spaces from children. The methodology is based in a qualitative approach of ethnographic inspiration, employing participatory and visual approaches. The study was carried out with 29 children, being 13 boys and 16 girls. However, a systematic monitoring was conducted with 08 children from a vulnerable area that circulate with autonomy in the city. The field work was organized in 4 moments: (i) mapping of public spaces where children were present to define possible participants; (ii) an approximation with children and their families; (iii) following of children in their moments of daily circulation in the public spaces of the city, such as leisure, events, parties and way to school, and;(iv) holding workshops. Aspects relating to children's circulation and their presence in the city, especially through play, relationship with nature, heritage of cultural groups and public spaces have emerged in this research. The data pointed that social markers of difference interfere in children´s ways of exploring public spaces. The understanding of the ways of children living in the cities to participate in the urban space inspire this work. It can be seen in a double scale analysis, the children´s perspective and urban scale in small cities.